Heating of metallic biliary stents during magnetic hyperthermia of patients with pancreatic ductal adenocarcinoma: an in silico study. (31st December 2022) - Bottauscio, Oriano; Rubia-Rodríguez, Irene; Arduino, Alessandro; Zilberti, Luca; Chiampi, Mario; Ortega, Daniel
Abstract: Objective: To investigate the eddy current heating that occurs in metallic biliary stents during magnetic hyperthermia treatments and to assess whether these implants should continue to be an exclusion criterion for potential patients. Methods: Computer simulations were run on stent heating during the hyperthermia treatment of local pancreatic tumors (5–15 mT fields at 300 kHz for 30 min), considering factors such as wire diameter, type of stent alloy, and field orientation. Maxwell's equations were solved numerically in a bile duct model, including the secondary field produced by the stents. The heat exchange problem was solved through a modified version of the Pennes' bioheat equation assuming a temperature dependency of blood perfusion and metabolic heat. Results: The choice of alloy has a large impact on the stent heating, preferring those having a lower electrical conductivity. Only for low field intensities (5 mT) and for some of the bile duct tissue layers the produced heating can be considered safe. The orientation of the applied field with respect to the stent wires can give rise to the onset of regions with different heating levels depending on the shape that the stent has finally adopted according to the body's posture. Bile helps to partially dissipate the heat that is generated in the lumen of the bile duct, but not at a sufficient rate. Conclusion: The safety of patients with pancreatic cancer wearing metallic biliary stents during magnetic hyperthermia treatments cannot be fully assured under the most common treatment parameters.